NEW WORK: The New Motivation Patterns in Work-From-Anywhere and Their Modern HR Implications - Adilla Kustya Ulfa; Awanis Linati Haziroh; Partiwi Dwi Astuti; Tito Wira Eka Suryawijaya; Ahmad Reza; Ahmad Rudi Yulianto (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
Work From Anywhere (WFA) has emerged as a global trend reshaping traditional work paradigms and organizational management practices. Despite its increasing adoption, work motivation patterns among WFA employees remain insufficiently understood, particularly regarding the balance between intrinsic and extrinsic drivers. This study examines factors influencing work motivation in a WFA context, with specific attention to autonomy, flexibility, social support, and emerging motivational challenges. Adopting a pragmatic paradigm, this study employs a convergent parallel mixed-methods design, in which quantitative and qualitative data were collected concurrently and integrated at the interpretation stage. The quantitative component consists of a cross-sectional survey of 60 WFA employees in Indonesia, analyzed using descriptive statistics, correlation, and regression analysis. The results indicate that intrinsic motivation, particularly autonomy and flexibility, has a significant positive effect on job satisfaction (r = 0.65), whereas extrinsic motivation shows no significant impact. Team and supervisory support emerge as strong drivers of motivation (r = 0.71), while feelings of isolation and difficulties in maintaining work–life balance are identified as key motivational barriers. Qualitative findings further reveal how social disconnection under WFA arrangements undermines sustained motivation despite high autonomy. These findings suggest that organizations should prioritize relatedness-oriented HR strategies, such as structured social support systems, virtual collaboration practices, and clearly defined work–life boundaries. From a policy perspective, the study highlights the importance of frameworks that protect employee well-being, including the right to disconnect.